Cell and Signal Components of the Microenvironment of Bone Metastasis Are Affected by Hypoxia - Bendinelli, Paola (Int J Mol Sci, 2016)
Bone metastatic cells release bone microenvironment proteins, such as the matricellular protein SPARC (secreted protein acidic and rich in cysteine), and share a cell signaling typical of the bone metabolism controlled by Runx2. The megakaryocytes in the bone marrow engrafted by the metastases seem to be one of the principal microenvironment sources of the biological stimuli, implicated in the formation of an osteoblastic niche, and affecting metastasis phenotype and colonization. Educated platelets in the circulation might derive from megakaryocytes in bone metastasis. The evaluation of predictive markers in the circulating platelets might be useful for the stratification of patients for therapeutic purposes. The hypoxic environment in bone metastasis is one of the key regulators of the network of the biological soluble and structural components of the matrix. In bone metastatic cells under hypoxia, similar patterns of Runx2 and SPARC are observed, both showing downregulation. Conversely, hypoxia induces Endothelin 1, which upregulates SPARC, and these biological stimuli may be considered prognostic markers of bone metastasis in breast carcinoma patients.